Angiojet thrombolysis and vena cava filter insertion in a case of a duplicated inferior vena cava - Blackwood, Stuart (SAGE Open Med Case Rep, 2015)
OBJECTIVES: Duplication of the inferior vena cava (IVC) complicates interventional procedures. This case report aims to shed light on this unusual anomaly and the preoperative considerations necessary when treatment of venous thromboembolism is undertaken. METHODS: An IRB approved case report of a 58 year old woman presented emergently with right lower extremity phlegmasia due to extensive thrombosis of her right iliofemoral and infrarenal portion of her duplicated IVC. RESULTS: The patient underwent IVC filter placement and rheolytic thrombectomy with thrombolysis using the Angiojet device followed by venoplasty and stenting of the iliofemoral system and right IVC. Complete symptomatic and radiographic resolution on duplex imaging was achieved at 1 year follow up. CONCLUSIONS: With adequate preoperative awareness of IVC anomalies and treatment options available satisfactory results can be achieved and complications minimized for this unique patient population.